2022
DOI: 10.1002/admt.202200173
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Metrology for Roll‐To‐Roll and Advanced Inline Manufacturing: A Review

Abstract: Roll‐to‐Roll (R2R) manufacturing is changing how state‐of‐the‐art technology is made. Roll‐to‐Roll is part of a family of advanced scalable inline manufacturing techniques that make traditional and state‐of‐the‐art products at high yield and reduced cost. R2R manufacturing has grown rapidly and is fundamental to several advanced technologies such as functional materials and films, sensors for medicine, biology, and environment monitoring, energy harvesting devices, and flexible electronics. Advantages of R2R m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 135 publications
(227 reference statements)
0
3
0
Order By: Relevance
“…A continuous R2R production can be evolved by additive processes, printing, and self-assembly [ 117 ]. New quality control and metrology forms are needed to store, monitor, and analyze real-time production data [ 118 ]. Process drift can be corrected in real time using artificial intelligence and other deep-learning techniques [ 119 ].…”
Section: Device Components and Their Use In Printed Photonic Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…A continuous R2R production can be evolved by additive processes, printing, and self-assembly [ 117 ]. New quality control and metrology forms are needed to store, monitor, and analyze real-time production data [ 118 ]. Process drift can be corrected in real time using artificial intelligence and other deep-learning techniques [ 119 ].…”
Section: Device Components and Their Use In Printed Photonic Devicesmentioning
confidence: 99%
“…Future inline metrology will increasingly incorporate techniques derived from big data analysis. They provide instant morphology for a wide variety of materials and products, with a spatial resolution on the order of 10 μm and requiring minimal calibration [ 118 ]. It has been reported that eddy current sensors are the best choice for noncontact inline R2R electrode quality monitoring [ 120 ].…”
Section: Device Components and Their Use In Printed Photonic Devicesmentioning
confidence: 99%
See 1 more Smart Citation